Skip to content

Advertisement

  • Research
  • Open Access

Stability properties and existence theorems of pseudo almost periodic solutions of linear Volterra difference equations

Advances in Difference Equations20122012:58

https://doi.org/10.1186/1687-1847-2012-58

  • Received: 2 November 2011
  • Accepted: 9 May 2012
  • Published:

Abstract

The purpose of this article is to discuss the existence of pseudo almost periodic solutions of linear Volterra equation: x ( n + 1 ) = A ( n ) x ( n ) + s = - n F ( n , s ) x ( s ) + p ( n ) , n Z, by using an exponentially stable of the zero solution, which is equivalent to the exponential behaviors of the resolvent matrix G(n, m) as n → ∞ and of some summability of the kernel.

AMS (MOS) 2000 Subject classifications: 39A11.

Keywords

  • Periodic Solution
  • Difference Equation
  • Periodic Function
  • Initial Function
  • Integrodifferential Equation

1 Introduction

For the difference equations and functional difference equations, the existence of almost periodic solutions of almost periodic systems has been studied by many authors. One of the most popular method is to assume the certain stability properties ([15]; T Itokazu and Y Hamaya, unpublished work). Recently, [68] have shown the existence of pseudo almost periodic solutions of difference equations, differential equations, and abstract differential equations. On the other hand, in the case of almost periodic solutions of linear Volterra systems, [3] has shown that if the zero solution of the linear Volterra equation is uniformly asymptotically stable, then the system has a unique almost periodic solution. In this article, we shall give some characterizations for the exponentially asymptotically stable of the zero solution of equation and in order to obtain the existence theorem for a pseudo almost periodic solutions of linear Volterra difference equations, we discusse to improve Hamanaka and Hamaya's result [4], for Volterra integro differential equations, to theorems for pseudo almost periodic linear Volterra difference equations.

To be best of author's observation, no article has been published regarding the investigation of pseudo almost periodicity of a linear Volterra difference equation with infinite delay. Thus, our results are presents a new originality for Volterra type difference equations.

Let R l denotes the l-dimensional Euclidean space, Z is the set of integers, Z+, Z - are the set of nonnegative and nonpositive integers, respectively, and |x| will denote the norm of x in R l . For any interval J Z, we denote by BS = BS(J : R l ) the set of all bounded functions mapping J into R l and set |ϕ| J = sup{(s)| : s J} for ϕ BS. In this article, all interval are discrete, e.g., [0, n0] = {0, 1, 2,..., n0}, n0 Z+.

We first introduce an almost periodic function f(n) : ZR l .

Definition 1. f(n) is said to be almost periodic in n (in short, f AP (Z)), if for any ε > 0, there exists a positive number L*(ε) such that any interval of length L*(ε) contains a τ Z for which
| f ( n + τ ) - f ( n ) | ε
(1)

for all n Z. Such a number τ in (1) is called an ε-translation number of f(n).

In order to formulate a property of almost periodic functions, which is equivalent to the above definition, we discuss the concept of the normality of almost periodic functions. Namely, let f(n) be almost periodic in n. Then, for any sequence { h k } Z , there exists a subsequence {h k } of { h k } and function g(n) such that
f ( n + h k ) g ( n )
(2)
uniformly on Z as k → ∞. We shall denote by T(f) the function space consisting of all translates of f, that is, f τ T (f), where
f τ ( n ) = f ( n + τ ) τ Z .
(3)

Let H(f) denotes the closure of T(f) in the sense of (3). H(f) is called the hull of f. In particular, we denote by Ω(f) the set of all limit functions g H(f) such that for some sequence {n k }, n k → ∞ as k → ∞ and f(n + n k ) → g(n) uniformly on Z. By (2), if f : ZR l is almost periodic in n, so is a function in Ω(f).

The following concept of asymptotic almost periodicity was introduced by Frechet (cf. [5]).

Definition 2. Let x : Z [a, ∞) → R l be a bounded function. x(n) is said to be asymptotically almost periodic if it is a sum of an almost periodic function p(n) and a function q(n) defined on J* = [a, ∞) Z+ which tends to zero as n → ∞, that is,
x ( n ) = p ( n ) + q ( n ) .

x(n) is asymptotically almost periodic if and only if for any sequence {n k } such that n k → ∞ as k → ∞ there exists a subsequence { n k j } for which x ( n + n k j ) converges uniformly on an < ∞.

We now set
P A P 0 ( Z ) = f B S ( Z ) : lim r 1 2 r n = - r r | f ( n ) | = 0 .

We next introduce new concept of pseudo almost periodic function.

Definition 3. f(n) is said to be pseudo almost periodic if
f = f 1 + f 0

where f1 AP(Z) and f0 PAP0(Z). f1 and f0 are called the almost periodic component and ergodic perturbation, respectively, of function f. We denote by PAP(Z) the set of all such function f.

Example 1. Let
f ( n ) =  sin  n + 1 n 2 + 1 .

Then, f PAP(Z).

2 Existence of Pseudo almost periodic solutions

Set |A| denotes the matrix norm of any l × l matrix A, where A(n) is an l × l matrix of functions for n Z, and let F(n, s) be an l × l matrix of functions for -∞ < sn < ∞, s Z. p(n) is a bounded function for n Z. We consider the equations
x ( n + 1 ) = A ( n ) x ( n ) + s = 0 n F ( n , s ) x ( s ) , n Z + ,
(4)
and
x ( n + 1 ) = A ( n ) x ( n ) + s = - n F ( n , s ) x ( s ) , n Z .
(5)
Moreover, we consider the perturbed system of
x ( n + 1 ) = A ( n ) x ( n ) + s = 0 n F ( n , s ) x ( s ) + p ( n )
(6)
such that x(n) = ϕ(n) for n [0, n0], and consider the following system of
x ( n + 1 ) = A ( n ) x ( n ) + s = - n F ( n , s ) x ( s ) + p ( n )
(7)

such that x(n) = ϕ(n) for n (-∞, n0].

We assume the following conditions throughout this article:
( H1 ) sup n Z { | A ( n ) | + s = - n | F ( n , s ) | } = : L < , for some  L > 0

and

(H2) For any ε > 0 there exists an integer S := S(ε) > 0 such that s = - n - S | F ( n , s ) | < ε for all n Z.

Under the above conditions, given n0 Z+ := [0, ∞) (resp. n0 Z) and ϕ BS ([0, n0]) (resp. ϕ BS((-∞, n0])) there is one and only one function x(n) which satisfies Equation (4) (resp. Equation (5)) on [n0, ∞) and x(n) = ϕ(n) on [0, n0] (resp. (-∞, n0]) (cf. [2]). The above function x(n) is called a solution of Equation (4) (resp. Equation (5)) on [n0, ∞) through (n0, ϕ), and is denoted by x(n, n0, ϕ) of Equation (4) (resp. x(n, n0, ϕ) of Equation (5)).

In addition to (H1) and (H2), we assume the either (H30) or (H3) for Equations (5) and (7):

(H30) A(n) is an almost periodic in n Z and F (n, n + s) is an almost periodic in n Z uniformly for s Z- : (-∞, 0], that is, for any ε > 0 and any compact set K Z-, there exists a positive number L(ε, K) such that any interval of length L(ε, K) contains a τ for which |F(n, n + s) - F (n + τ, n + τ + s)| < ε for all n Z and s K,

or

(H3) A(n) is pseudo almost periodic and F (n, n + s) is pseudo almost periodic, that is F(n, n + s) = F1(n, n + s) + F0(n, n + s), where F1(n, n + s) satisfies almost periodicity in (H30) and F0(n, n + s) satisfies lim r 1 2 r n = - r r F 0 ( n , n + s ) | = 0 uniformly for s Z-.

In particular, since (A, F) H(A, F) by condition (H30), Equation (5) is one of limiting equations of Equation (4).

Let G(n, s) < ∞, -∞ < sn < ∞, be the unique matrix solution of
G ( n + 1 , s ) = A ( n ) G ( n , s ) + r = s n F ( n , r ) G ( r , s ) , n s , G ( s , s ) = I ,
(8)

where I is the l × l unit matrix and G(n, s) ≡ 0 for n < s. G(n, s) is called the resolvent matrix of (4).

The solution x(n, 0, ϕ0) of (6) through (0, ϕ0) is expressed by the variation of parameters formula as
x ( n , 0 , ϕ 0 ) = G ( n , 0 ) ϕ 0 + s = 0 n - 1 G ( n , s + 1 ) p ( s ) .
Then, we have
x ( n + n 0 , n 0 , ϕ ) G ( n + n 0 , n 0 ) ϕ ( n 0 ) + s = 0 n - 1 G ( n + n 0 , n 0 + s + 1 ) × r = 0 n 0 - 1 F ( s + n 0 , r ) ϕ ( r ) + p ( s + n 0 ) = G ( n + n 0 , n 0 ) ϕ ( n 0 ) + s = 0 n G ( n + n 0 , n 0 + s + 1 ) × r = 0 n 0 - 1 F ( s + n 0 , r ) ϕ ( r ) + p ( s + n 0 )
for n ≥ 0. The solution x(n, n0, ϕ) of (7) through (n0, ϕ) satisfies the equation
x ( n + 1 ) = A ( n ) x ( n ) + s = 0 n F ( n , s ) x ( s ) + s = - - 1 F ( n , s ) ϕ ( s ) + p ( n ) , n n 0 .
Thus, we have similar the expression
x ( n + n 0 , n 0 , ϕ ) G ( n + n 0 , n 0 ) ϕ ( n 0 ) + s = 0 n - 1 G ( n + n 0 , n 0 + s + 1 ) × r = - n 0 - 1 F ( s + n 0 , r ) ϕ ( r ) + p ( s + n 0 ) , n 0 .

Throughout this article, we employ the following definitions of stability.

Definition 4. The zero solution of Equation (4) (resp. Equation (5)) is said to be exponentially stable (in short, ExS), if there exists λ > 0, δ > 0 and η (0, 1) such that | ϕ | = | ϕ | [ 0 , n 0 ] < δ ( resp . | ϕ | = | ϕ | ( - , n 0 ] < δ ) implies
| x ( n , n 0 , ϕ ) | λ | ϕ | η n - n 0 for all  n n 0 ,

where x(n, n0, ϕ) is a solution of Equation (4) (resp. Equation (5)) through (n0, ϕ).

Definition 5. The zero solution of Equation (4) (resp. Equation (5)) is said to be; (i) uniformly stable (in short, US), if for any ε > 0 there exists a δ(ε) > 0 such that | ϕ | [ 0 , n 0 ] < δ ( ε ) ( resp . | ϕ | ( - , n 0 ] < δ ( ε ) ) implies | x ( n , n 0 , ϕ ) | < ε for all nn0, where x(n, n0, ϕ) is a solution of Equation (4) (resp. Equation (5)) through (n0, ϕ).
  1. (ii)

    uniformly asymptotically stable (in short, UAS), if it is US and moreover, if there is a δ 0 > 0 with the property that for any ε > 0 there exists a T (ε) > 0 such that n 0 Z and ϕ with | ϕ | [ 0 , n 0 ] < δ 0 ( resp . | ϕ | ( - , n 0 ] < δ ) imply |x(n, n 0, ϕ)| < ε for all nn 0 + T (ε), where x(n, n 0, ϕ) is a solution of Equation (4) (resp. Equation (5)) through (n 0, ϕ).

     
  2. (iii)

    totally stable (in short, TS), if for any ε > 0 there exists a δ(ε) > 0 such that | ϕ | [ 0 , n 0 ] < δ ( ε ) ( resp . | ϕ | ( - , n 0 ] < δ ( ε ) ) and that p : [n 0, ∞) → R l is defined any function with | p | [ n 0 , ] < δ ( ε )  implies | x ( n , n 0 , ϕ ) | < ε for all nn 0, where x(n, n 0, ϕ) is a solution of pertubed Equation (6) (resp. Equation (7)) through (n 0, ϕ).

     

By Definitions 4 and 5, it is clear that if the zero solution of Equation (4) (resp. Equation (5)) is ExS, then it is UAS.

We now consider that the following Lemma 1, which is a relationship between the zero solution of ExS for Equation (4) and the zero solution of ExS for Equation (5) (cf. [3]), and moreover the following Theorem 1 is known for the integrodifferential equation [4], however we shall write this theorem to difference equations and convenience for the proof of Theorem 2.

Lemma 1. Under the conditions (H1), (H2), and (H3), if the zero solution of Equation (5) is ExS, then the zero solution of Equation (4) is ExS.

Theorem 1. Suppose that conditions (H1) and (H2) hold. The zero solution of Equation (4) is ExS, if and only if there are positive constants M and μ (0, 1) such that
| G ( n , s ) | M μ ( n - s ) and | e ( n , s ) | M μ ( n - s ) for all  n s 0 .
(9)

Here, G(n, s) and e ( n , s ) : = r = 0 s - 1 | θ = s n G ( n , θ + 1 ) F ( n , r ) | are called the exponential decay (in short, ExD).

Proof

We first prove G(n, s) and e(n, s) are ExD. Assume that the zero solution of Equation (4) is ExS. Let δ be the corresponding constant of exponential stability. Let s be any fixed nonnegative integer and v be any fixed vector with |v| < δ. Define a sequence {τϕmτ}, m = 1, 2, . . . of functions by
ϕ m = 0 for 0 u 1 - 1 m 2 s m s u - 1 - 1 m 2 s v for 1 - 1 m 2 s u s ,

where [w] denotes the greatest integer of the real number w. For any positive integer m and u 1 - 1 m 2 s , s , | m s u - 1 - 1 m 2 s v | < δ . Hence, ϕm BS([0, s], B δ ) for m = 1, 2,..., where B δ = {x R l : |x| < δ}.

For initial functions such as above ϕm, Equation (4) can be written in the form
x ( n + 1 ) = A ( n ) x ( n ) + r = s n F ( n , r ) x ( r ) + h m ( n ) ,

where h m ( n ) = r = 0 s - 1 F ( n , r ) ϕ m ( r ) for ns.

From the variation of parameters formula, the solution x m (n) is given by
x m ( n ) = G ( n , s ) ϕ m ( s ) + θ = s n - 1 G ( n , θ + 1 ) h m ( θ )  for  n s ,
(10)

where ϕm(s) = v for m = 1, 2, . . .

Therefore by assumption of ExS, the corresponding solutions x m (n) = x(n, s, ϕ m ) satisfy
| x m ( n ) | λ | ϕ | η ( n - s ) for  m = 1 , 2 ,
(11)

and for all ns, where λ is some positive constant and η (0, 1).

We consider the sequence functions {h m }. For θ [s, n],
h m ( θ ) = u = 0 s - 1 F ( θ , u ) ϕ m ( u ) = m s u = ( 1 - 1 m 2 ) s s - 1 u - 1 - 1 m 2 s F ( θ , u ) v = 1 ( s m ) u = s [ s - s m 2 ] ( u - s ) F ( θ , u ) v + 1 m u = [ s - 2 m 2 ] s - 1 F ( θ , u ) v .
It is clear that h m (θ) → 0 for sθn, as m → ∞. Since | G ( n , θ + 1 ) h m ( θ ) | δ | G ( n , θ + 1 ) | Σ u = 0 s - 1 | F ( θ , u ) | , we see that G(n, θ + 1)h m (θ) converges boundedly to zero on [s, n] as m → ∞; hence
θ = s n G ( n , θ + 1 ) h m ( θ ) 0 as  m
(12)

by convergence theorem.

For (10), we have
| G ( n , s ) v | | x m ( n ) | + | θ = s n G ( n , θ + 1 ) h m ( θ ) | ,

which implies that |G(n, s) v | ≤ λ |ϕ|η(n-s)by using (11) and (12).

With such initial functions as ϕm(s), we have lim m →∞x m (n) = G(n, s)v. The induced norm of G(n, s) is
| G ( n , s ) | = sup | w | 1 | G ( n , s ) w | = sup | v | δ | G ( n , s ) δ - 1 v | δ - 1 λ | ϕ | η ( n - s ) ,

for all vectors v with |v| < δ.

Therefore,
| G ( n , s ) | M 0 η ( n - s ) for  n s 0 ,

where M0 = λδ-1.

For s ≥ 0 and an initial function ϕ BS([0, s], B δ ), the solution x(n) = x(n, s, ϕ) is dominated by the function λη(n-s)for ns. If we defined h(n) = x(n) - G(n, s) ϕ(s), we hold that
| h ( n ) | | x ( n ) | + | G ( n , s ) | | ϕ ( s ) | λ η ( n - s ) + λ δ - 1 η ( n - s ) δ = 2 λ η ( n - s )

for ns.

This along with the variation of parameters formula, implies
r = 0 s - 1 θ = s n G ( n , θ + 1 ) F ( n , r ) ϕ ( r ) < 2 λ μ ( n - s )

for all ϕ BS([0, s], Bδ).

Regarding s and n as fixed for the moment and using the modify of results in [4], we have
r = 0 s - 1 θ = s n G ( n , θ + 1 ) F ( n , r ) < 2 M 1 δ - 1 λ μ ( n - s )

for some constant M1 > 0. Since M1 is independent of the choice of s and n, this holds for all ns≥0. If we define M = max{M0, 2M1M0}, then (9) is the result.

Conversely, we assume that there are positive constant μ (0, 1) and M such that (9) is true for μ = η . Let δ = λ/2M and η = μ. Then for any s ≥ 0 and initial function ϕ BS([0, s], B δ ), the variation of parameters formula show that the solutions x(n) = x(n, s, ϕ) is bounded as follows:
| x ( n ) | | G ( n , s ) | | ϕ ( s ) | + r = 0 s - 1 θ = s n G ( n , θ + 1 ) F ( n , r ) ϕ ( r ) | ϕ | [ 0 , n 0 ] × ( | G ( n , s ) | + e ( n , s ) ) 2 δ M μ n - s = λ μ n - s .
(13)

This proves the converse. q.e.d.

Theorem 2. Suppose that conditions (H1), (H2), and (H3) hold. If the zero solution of Equation (5) is ExS, then for p PAP(Z) the function s = - n G ( n , s + 1 ) p ( s ) is a Z-bounded and unique PAP (Z) solution of (7).

Proof.

From Lemma 1 and Theorem 1, if the zero solution of Equation (5) is ExS, then G(n, s) satisfies ExD. We can see that sup n 0 s = n | G ( n , s + 1 ) | < . Set
u ( n ) = s = - n G ( n , s + 1 ) p ( s ) .
We first prove the Z-boundedness of u(n).
| u | Z = s = - n G ( n , s + 1 ) p ( s ) s = - n | G ( n , s + 1 ) | | p ( s ) | | p | z s = - n | G ( n , s + 1 ) | .
Using the property of ExD for kernel G(n, s), we have
| u | Z | p | Z s = - n M μ ( n - 1 - s ) | p | Z M ( 1 - μ ) μ M ( 1 - μ ) μ ( | p 1 | Z + | P o | Z ) ,

where p(n) = p1(n) + p0(n), that p1(n) is almost periodic function and p0(n) is ergodic perturbation.

By the assumption for G(n, s),
s = n | G ( n , s + 1 ) | s = n M μ ( n 1 s ) ) N 0 ,

for all ns > - ∞, where N 0 : = M ( 1 - μ ) μ .

We second prove that u(n) satisfies the Equation (7) on Z. Indeed, we have
A ( n ) u ( n ) + s = - n F ( n , s ) u ( n ) + p ( n ) = r = - n A ( n ) G ( n , r + 1 ) p ( r ) + s = - n F ( n , s ) r = - s G ( s , r + 1 ) p ( r ) + p ( n ) = r = - n [ A ( n ) G ( n , r + 1 ) + s = r n F ( n , s ) G ( s , r + 1 ) ] p ( r ) + p ( n ) = r = - n - 1 [ A ( n ) G ( n , r + 1 ) + s = r n F ( n , s ) G ( s , r + 1 ) ] p ( r ) + p ( n ) = r = - n - 1 G ( n + 1 , r + 1 ) p ( r ) + p ( n ) = r = - n G ( n + 1 , r + 1 ) p ( r ) = u ( n + 1 )

for all n Z+.

We next prove the uniqueness of solution. Assume that Equation (7) has two bounded solutions x1 and x2. Then z = x1 - x2 is a bounded solution for the linear Volterra Equation (5).

Then, by (13), we have
| z ( n ) | 2 M μ ( n - s ) | ϕ | Z .

Since z is bounded, we can take a near infinity and consequently we have z(n) = 0, thus x1 = x2, which gives the uniqueness property.

We now have a decomposition
u ( n ) = s = - n G ( n , s + 1 ) p 1 ( s ) + s = - n G ( n , s + 1 ) p 0 ( s ) : = u 1 ( n ) + u 0 ( n ) ,
since p PAP (Z) and p(n) = p1(n) + p0(n), where p1 AP (Z) and p0 PAP0(Z). Then, u 1 = s = - n G ( n , s + 1 ) p 1 ( s ) is an almost periodic function. Indeed, for any ε > 0, there is lε(ε) > 0 such that, for all ρ Z, there exists τ [ρ, ρ + lε(ε)] with sup n Z |p1(n+τ) - p1(n)| ≤ ε. It follows that sup n Z |u1(n + τ) - u1(n)| ≤ εM/(1 - μ)μ then u1 is almost periodic. In order to show that u PAP(Z), we need to show that u0 PAP0(Z), that is we suffice to show that
lim r 1 2 r n = - r r | u 0 ( n ) | = 0 .
(14)
We have
0 lim r 1 2 r n = - r r | u 0 ( n ) | lim r M 2 r n = - r r s = - n μ ( n - 1 - s ) | p 0 ( s ) | = lim r M 2 r n = - r r 1 ( 1 - μ ) μ | p | Z lim r M 2 r 1 ( 1 - μ ) μ n = - r r | p | Z .

Since -rnr, then 1 ( 1 - μ ) μ is bounded. Furthermore, p0 PAP0(Z) then (14) yields.

This completes the proof of Theorem 2. q.e.d.

Remark 1. Theorem 2 is corresponding to linear Volterra integrodifferential equations with adequate modification [4].

We assume that (H3) is replaced by (H30),

For the nonlinear equation, (T Itokazu and Y Hamaya, unpublished work) has established that if the bounded solution u(n) of
x ( n + 1 ) = f ( n , x ) + s = - n F ( n , s , x ( s ) )
(15)

is totally stable then it is (K, ρ)-totally stable, and it is also well known that if the bounded solution u(n) of Equation (15) is (K, ρ)-totally stable, then it is (K, ρ)-stable under disturbances from Ω(f), and we have an almost periodic solution of Equation (15) (cf. [4]; T Itokazu and Y Hamaya, unpublished work).

Now, for Equation (15), we assume the following conditions;
( H 1 ) sup n Z { | f ( n , x ( n ) ) | + Σ s = - n | F ( n , s , x ( s ) ) | } = : L < ,  for some  L > 0 ,

(H2') For any ε > 0 there exists an integer S := S(ε) > 0 such that s = - n - S F ( n , s , x ( n ) ) < ε for all n Z

and

(H3') f(n, x) is pseudo almost periodic in n uniformly for x R l , and F (n, s, x) is pseudo almost periodic in n uniformly for x any compact set K R l .

Moreover, we have the following conjecture for Equation (15).

Conjecture. Under the assumptions (H1'), (H2'), and (H3'), if the bounded solution u(n) of Equation (15) is (K, ρ)-exponential asymptotically stable, then Equation (15) has a pseudo almost periodic solution.

Author now has not enough time to prove above conjecture.

On the other hand, for our linear equation we have the following results.

Theorem A[3]. Under the assumptions (H1), (H2), and (H30), if the zero solution u(n) of Equation (5) is UAS, then the Equation (7) has an almost periodic solution whenever p(n) is almost periodic in n Z.

Proof. UAS of u(n) implies UAS in hull solution by Lemma 3 in [3], then one has an almost periodic solution of Equation (7) by Theorem 3 and Corollary 2 in [3].

3 Example

We consider the following pseudo almost periodic system:
x ( n + 1 ) = A ( n ) x ( n ) + s = - n F ( n , s ) x ( s ) + p ( n ) ,
(16)
equivalently,
x ( n + 1 ) = A ( n ) x ( n ) + s = - 0 F ( n , n + s ) x ( n + s ) + p ( n ) ,
where
A ( n ) = - 1 + 3 2 co s 2 n 1 - 3 2 cos  n sin  n - 1 - 3 2 cos  n sin  n - 1 + 3 2 si n 2 n ,
p ( n ) = cos n sin n  is almost periodic,
and
F ( n , n + s ) = ( cos 2 n + 1 n 2 + 1 ) μ n - ( n + s ) 0 0 ( sin 2 n + 1 n 2 + 1 ) μ n - ( n + s ) .

A(n) is almost periodic and the eigenvalues λ1(n) and λ2(n) of A(n) are λ 1 ( n ) = - 1 + 7 i 4 , λ 2 ( n ) = - 1 - 7 i 4 , and in particular the eigenvalues are in the unit circle.

Then, the zero solution of the system x(n + 1) = A(n)x(n) is an ExS. Moreover, the zero solution of x ( n + 1 ) = A ( n ) x ( n ) + s = - 0 F ( n , n + s ) x ( n + s ) is an ExS by our assumptions (cf. [3, 4, 9]).

A(n) is almost periodic and thus pseudo almost periodic. F (n, n + s) is a sum of almost periodic function F 1 ( n , n + s ) = cos 2 n 0 0 sin 2 n μ - s and F 0 ( n , n + s ) = 1 n 2 + 1 0 0 1 n 2 + 1 μ - s is an ergodic perturbation, because
lim r 1 2 r n = - r r | F ( n , n + s ) | = lim r 1 2 r n = - r r μ - s n 2 + 1 = μ - s lim r 1 2 r n = - r r 1 n 2 + 1 μ - s lim r 1 2 r C 0 = 0 uniformly  s Z - ,

for some constant C0 > 0. Thus, by Theorem 2, Equation (16) have a pseudo almost periodic solution x(n).

Declarations

Acknowledgements

The author would like to express his gratitude to the referee and the editors for their many helpful comments.

Authors’ Affiliations

(1)
Department of Information Science, Okayama University of Science, 1-1 Ridai-chyo, Kitaku Okayama, 700-0005, Japan

References

  1. Elaydi S: Periodicity and stability of linear Volterra difference systems. J Math Anal 1994, 181: 483–492. 10.1006/jmaa.1994.1037MathSciNetView ArticleGoogle Scholar
  2. Elaydi S, Murakami S: Asymptotic stability versus exponential stability in linear Volterra difference equations of convolution type. J Diff Equ Appl 1996, 2: 401–410. 10.1080/10236199608808074MathSciNetView ArticleGoogle Scholar
  3. Elaydi S, Murakami S: Uniformly asymptotic stability in linear Volterra difference equations. J Diff Equ Appl 1998, 3: 203–218.MathSciNetView ArticleGoogle Scholar
  4. Hamanaka Y, Hamaya Y: Existence of pseudo almost periodic solutions of linear Volterra integrodifferential equations. Analele Stiintifice ale Universitatii 'Al. I. Cuza' Mathematica, Tomul 2011, LVII: 87–102.MathSciNetGoogle Scholar
  5. Yoshizawa T: Stability Theory and the Existence of Periodic Solutions and Almost Periodic Solutions, Applied Mathematical Sciences 14. Springer-Verlag, Berlin; 1975.View ArticleGoogle Scholar
  6. Ait Dads E, Ezzinbi K, Arino O: Pseudo almost periodic solutions for some differential equations in a banach space. Nonlinear Anal Theory Methods Appl 1997, 28: 1141–1155. 10.1016/S0362-546X(97)82865-9MathSciNetView ArticleGoogle Scholar
  7. Hong J, Nunez C: The almost periodic type difference equations. Mathl Comput Model 1998, 28: 21–31.MathSciNetGoogle Scholar
  8. Zhang C: Almost Periodic Type Functions and Ergodicity. Science Kluwer/Press and Academic Pubblishers, Dordrecht 2003.Google Scholar
  9. Elaydi S: An Introduction to Difference Equations. 3rd edition. Springer, Berlin; 2005.Google Scholar

Copyright

© Hamaya; licensee Springer. 2012

This article is published under license to BioMed Central Ltd. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Advertisement